The Utilization of Adobe Flash in Increasing Student Learning Motivation in Subjects in Elementary - Marni Marni (Universitas Tanjungpura, 2021)
This study aims to determine: (1) the competence of teachers in using learning media before implementing adobe flash guidance at SDN (Public Elementary School) 42 Sungai Ambawang, (2) teacher competence in using learning media after implementing adobe flash guidance at SDN 42 Sungai Ambawang, (3 ) Increasing teacher competence in using learning media after adobe flash guidance was carried out at SDN 42 Sungai Ambawang. This type of research was action research conducted at SDN 42 Sungai Ambawang. The results of the study conducted showed that: (1) The teacher's competence in using learning media before the adobe flash guidance was carried out at SDN 42 Sungai Ambawang based on the observation results was in low qualification and only reached 1.98 and based on the results of the questionnaire it was in low qualification and only reached 155%, (2) Based on the results of the implementation of the first cycle, it showed that the average observation result of teacher competence in using learning media after adobe flash guidance was carried out at SDN 42 Sungai Ambawang reached 2.78 and entered moderate qualifications and the results of the questionnaire showed an average 45% and enter moderate qualification. While the implementation of the second cycle based on observation data reached 3.48 and entered the High qualification and the results of the questionnaire reached 70% and entered the high qualification, (3) Increased teacher competence in using learning media after adobe flash guidance was carried out at SDN 42 Sungai Ambawang, namely an increase in the results observation.